Enhancing rice husk ash-based aluminosilicate fire retardant additive as a passive fire protection material - Abdullah, Mohd Na'im (2021)
Several major research studies have concluded that most fire retardants (FR) are associated with numerous environmental and human health concerns, which led them to be replaced by more eco-friendly alternatives. Since Malaysia has been producing abundant of rice husk (RH), the utilisation of rice husk ash (RHA) as an aluminosilicate source in fire-resistant coating could reduce the environmental pollution and can turn agricultural waste into industrial wealth. The main objective of this research is to develop an eco-friendly RHA-based aluminosilicate FR additive. Four experiments were conducted; namely fire resistant, tensile, adhesion, and water absorption tests to assess the microstructure behavior of the developed RHA-based aluminosilicate FR additive. Response surface methodology (RSM) was used to design the experiments incorporating two factors; namely ratio of FR additive to paint and their interrelationship and effect on FR coating properties were analysed using analysis of variance (ANOVA). The relationship of different pre-treatment on the production of silica content from RH were also studied to understand the relationship of each pre-treatment on the produced silica content from RHA. From the fire resistance test and scanning electron microscopy images, higher ratio of RHA-based aluminosilicate contributed a better fire protection efficiency due to the formation of thicker char layer thickness which affected the equilibrium temperature. For both tensile and adhesion strength, the addition of RHA-based aluminosilicate FR improved the ultimate tensile strength and adhesion strength due to dense gel phase which has a well-connected structure and less unreacted particles on the surface coating. However, major drawback on the addition of RHA-based aluminosilicate is the enhancement of water permeation which led to the deterioration of the coating samples. Thus, it can be summarized that silica efficiently improved the strength and compactness of the char layer, which resulted in a relatively higher fire retardant efficiency. In this research, RHA proved to be a good aluminosilicate source alternative for fire retardant additive due to its intumescent process, which can potentially improve building fire safety through passive fire protection.